Improving Employee Performance Through Spiritual Leadership, Moderated by Workplace Spirituality at PT Carma Wira Jatim - Romi Tantio Wicaksono; Alifah Ratnawati (CV. Publikasi Indonesia, 2026)
This study aims to analyze the application of spiritual leadership at PT Carma Wira Jatim and examine its effect on improving employee performance, with workplace spirituality as a moderating variable. Current leadership practices in the industry tend to focus on rationality and efficiency, often overlooking employees' needs for meaning, intrinsic motivation, and work-life balance. Using a mixed methods sequential explanatory approach, the first stage applied a quantitative method to 101 permanent and contract employees through closed questionnaires measured with a 1–5 Likert scale. Data were analyzed using multiple linear regression and moderation tests with SmartPLS. The second stage used a qualitative approach through semi-structured interviews with 5–7 purposively selected informants to explore the context and meaning of spirituality in the workplace. The study addresses the research gap in spiritual leadership studies based on Islamic values within local manufacturing industries. The results are expected to provide theoretical contributions to management science and practical recommendations for PT Carma Wira Jatim to implement more effective spiritual leadership, fostering a meaningful, religious, and sustainable work environment that improves employee welfare and organizational performance.